ANALISIS KETERAMPILAN BERPIKIR KRITIS SISWA KELAS VII PADA MATERI PEMANASAN GLOBAL DI MTS ALMUTTAQIN PEKANBARU - A, Fitriana Ratih; Nasir, Muhammad; Azhar, Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the level of critical thinking skills of class VII MTs Al-Muttaqin Pekanbaru students on the subject of global warming. The subjects in this study were all VII grade students, consisting of four classes totaling 148 students. The research instrument was consist form of a test of critical thinking skills which was compiled based on 6 indicators of critical thinking skills namely interpretation, analysis, inference, evaluation, explanation and self regulation. Trial tests have been conducted at MTs Darel Fadhilah and the trial test participants consisted of 25 students. The results of the question validation using biserial points obtained 6 invalid questions, so the questions were rejected, while for reliability using KR21 and the reliability value was 0.8199. Data is collected by giving tests to all students who have studied the material of global warming. Data analysis in this study uses descriptive analysis that provides an overview of the level of critical thinking skills group into high, medium and low groups. The results showed that 114 students were included in the group of moderate critical thinking skills, 22 students in the low group and 12 high group students. Indicators that have high value are indicators of analysis. The class that has high critical thinking skills is class VIIB.Key Words: Critical thinking skills, global warming.